Interactional Competence and Gender Impacts on EFL Learners’ Self-Perceptions of Its Sub-Constructs - Zari Saeedi; Hossein Jajarmi (Journal of Modern Research in English Language Studies)
Even though interactional competence (IC) has recently been at the center of attention, its constructs/sub-components and influencing factors still require profound scrutiny. The features associated with IC have indeed been probed in various language learning and teaching realms. However, the effect of language learners’ gender on their perception of IC remains to be addressed. To bridge this gap, the present research, as one of the stages of development and verification of the Learners’ Interactional Competence Questionnaire (LICQ), investigated how gender may affect IC and its sub-constructs as perceived by males and females. A total of 407 male and female intermediate-level Iranian EFL learners, selected through convenience sampling from several language institutes, participated in the study and responded to the LICQ. Subsequently, a twogroup multivariate analysis of variance (MANOVA) was used to measure the potential effects of students’ gender on perceived IC, including conversational management, speech acts, register, nonverbal semiotics, and requests and complaints. The results showed that gender has a small significant effect on learners’ perceived interactional competence. Even though this effect is not visible in conversational management, but exists in the other four sub-components, namely speech acts, register, nonverbal semiotics, and requests and complaints. Language teachers could consider the different perceptions of male and female learners of IC as an influential aspect of IC realization and development in the language classroom setting. Besides, the study findings provide learners with a selfassessment scale to identify their present state of IC perception and monitor its development through time.